Formación para el trabajo, claves pedagógicas para la educación en Colombia (2017)
The following research was done from a documentary tracing, from different studies and authors that talk about the formation for the work in Colombia in the century XX. From this process an objective was raised which tries to: build in key of pedagogy a history of training for work in Colombia. The qualitative method was used with a type of descriptive study and as instrument a tab of contents in which the information found was stored. The results of this research were the construction of three chapters which are: History of education in Colombia, the body in training for work, physical education and training for work. From an order of ideas and having many clear concepts it was possible to conclude that education contributes partially to the consolidation of a knowledge society.